A Qualitative Study of Women's Experiences with Cognitive-Behavioral and Mindfulness-Based Online Interventions for Low Sexual Desire. Issue 9 (22nd November 2022) - Meyers, Milena; Margraf, Jürgen; Velten, Julia
ABSTRACT: Cognitive-behavioral (CBT) and mindfulness-based therapy (MBT) are among the most researched types of psychological interventions for low sexual desire in women. While both have been found effective in improving women's sexual desire, little is known about how women personally experience these treatments. To closely examine both approaches from a participant's perspective, semi-structured telephone-based interviews were conducted with 51 cis-women ( M age = 39, SD = 11, range = 22 to 69) who participated in a randomized controlled study comparing internet-based CBT and MBT for low sexual desire with a waitlist. Interview data were analyzed using thematic and content analysis. Most women ( n = 44, 86.3%) evaluated their respective treatment (i.e., CBT or MBT) as helpful in improving their sexual desire. CBT-techniques, such as cognitive restructuring, were mentioned as being helpful for challenging maladaptive thinking patterns, while formal mindfulness-exercises allowed women to disengage from negative sexuality-related thoughts. Elements of sex therapy, including self-stimulation exercises and sensate focus, were perceived as crucial for getting women in touch with their sexual desires and preferences. Strengths of the online format included anonymity, flexibility, and convenient access. Overall, women's personal accounts supported feasibility, acceptability, and clinical usefulness of CBT- and MBT-based internet interventions targeting low sexual desire.